2021
DOI: 10.1016/j.mayocp.2020.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Multitarget Stool DNA Testing vs Colonoscopy or Fecal Immunochemical Testing for Colorectal Cancer Screening in Alaska Native People

Abstract: Objective: To estimate the cost-effectiveness of multitarget stool DNA testing (MT-sDNA) compared with colonoscopy and fecal immunochemical testing (FIT) for Alaska Native adults. Patients and Methods: A Markov model was used to evaluate the 3 screening test effects over 40 years. Outcomes included colorectal cancer (CRC) incidence and mortality, costs, quality-adjusted life-years (QALYs), and incremental cost-effectiveness ratios (ICERs). The study incorporated updated evidence on screening test performance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 116 publications
0
32
0
Order By: Relevance
“…H. pylori is also associated with hemorrhagic gastritis, which can cause false‐positive results in fecal occult blood tests (FOBT) 90,91 ; consequently, despite their potential utility in this rural population, FOBT is not recommended for CRC screening in Alaska Native individuals 92 . The Alaska Tribal Health System has prioritized access to endoscopic services 92 and, more recently, multitarget stool DNA testing (Cologuard; Exact Sciences Corporation), which is the most cost‐effective and effective screening method for this population 93 . As a result of these efforts, CRC screening rates in IHS facilities in Alaska 94 (59%) were higher than in any other PRCDA region in 2017 (Table 4), although earlier stage diagnosis and reduced mortality have yet to be achieved 85 …”
Section: Selected Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…H. pylori is also associated with hemorrhagic gastritis, which can cause false‐positive results in fecal occult blood tests (FOBT) 90,91 ; consequently, despite their potential utility in this rural population, FOBT is not recommended for CRC screening in Alaska Native individuals 92 . The Alaska Tribal Health System has prioritized access to endoscopic services 92 and, more recently, multitarget stool DNA testing (Cologuard; Exact Sciences Corporation), which is the most cost‐effective and effective screening method for this population 93 . As a result of these efforts, CRC screening rates in IHS facilities in Alaska 94 (59%) were higher than in any other PRCDA region in 2017 (Table 4), although earlier stage diagnosis and reduced mortality have yet to be achieved 85 …”
Section: Selected Findingsmentioning
confidence: 99%
“…Access to colonoscopy and multitarget stool DNA tests 93,186 for CRC screening is of particular importance for Alaska Native individuals because of their high risk for the disease and for H. pylori‐associated hemorrhagic gastritis, 90,91 which can cause false‐positive fecal occult blood tests 92 . Alaska Native individuals face many challenges in obtaining colonoscopy services, including transportation barriers because many Alaska Native individuals live in areas that lack road networks.…”
Section: Selected Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the sensitivity of the FIT, which has been proven to be useful in the diagnosis of advanced adenomas, is limited to 5%-16% in the diagnosis of sessile serrated lesions, which account for 25%-30% of sporadic CRC precursors [40,41]. Therefore, there have been attempts (e.g., multitargeted fecal DNA test) to increase the sensitivity and specificity of stool tests by targeting tumor metabolites and genes rather than blood in the feces [42][43][44][45].…”
Section: Screening Testsmentioning
confidence: 99%
“…Previous research has shown increases in screening adherence among patients who use mt-sDNA, even among those who have never been screened, as well as an improvement in the quality of follow-up colonoscopies [ [17] , [18] , [19] ]. In previous research, our team demonstrated high sensitivity of mt-sDNA for cancer and large polyps among AN adults [ 16 ], interest in using mt-sDNA among AN patients and their healthcare providers [ 20 ], and that mt-sDNA is a cost-effective screening strategy in this population [ 21 ]. However, it is unknown if mt-sDNA is feasible in rural/remote AN communities, and whether use of mt-sDNA will actually increase AN CRC screening adherence.…”
Section: Introductionmentioning
confidence: 99%